PENGEMBANGAN MEDIA PEMBELAJARAN GAULL (GAME EDUKASI WORDWALL) PADA MATERI HAK DAN KEWAJIBAN KELAS V UPT SD NEGERI 065003 MEDAN LABUHAN - Elviyani; Irfan Dahnial (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
For primary school civics lessons to be engaging, children need to be able to take part. Making engaging educational game-based learning material that students can use to apply what they've learned is one way to make this happen. So, with two goals in mind, researchers created wordwall learning material. They are interested in two things: first, making a GAULL (Wordwall Educational Game) product or piece of learning media, and second, finding out whether that piece of media is legitimate from a rights and obligations standpoint. Research and development (R&D) employs the 4 D model of development proposed by Thiagarajan in this context. Researchers in this study only implemented three stages of 4D development for GAULL learning media (Wordwall Educational Game) in Theme 4, sub-theme 1, "Rights, Obligations and Responsibilities," since this was the only theme that was determined to be applicable to the learning process. something people find intriguing. The data collection tool is a questionnaire that is sent to validators, who are professionals in the fields of media and materials. Media expert validation yielded a 95% score, whereas material expert validation yielded a 96% score. Thus, 95% is the average score of the two validators. with the goal of establishing "very valid" standards based on the findings of the two experts. The GAULL learning medium, which is an educational game, falls within the "Rights, Obligations and Responsibilities" subtheme of Theme 4, and its development was deemed "very valid" for educational purposes.